Facile synthesis of bowl-like 3D Mg(BH4)2–NaBH4–fluorographene composite with unexpected superior dehydrogenation performances. Issue 20 (5th May 2017) - Zheng, Jiaguang; Xiao, Xuezhang; Zhang, Liuting; Li, Shouquan; Ge, Hongwei; Chen, Lixin
Abstract : Significantly improved hydrogen desorption behaviors are found in 3D bowl-like Mg(BH4 )2 –NaBH4 –FG composite. Abstract : A remarkable improvement in the hydrogen desorption performance of Mg(BH4 )2 –NaBH4 eutectic composite is achieved by simply ball-milling with fluorographene (FG). It is found that the desorption temperature of Mg(BH4 )2 –NaBH4 (∼200 °C) is still too high and liquid phase appears during dehydrogenation. Particularly, the novel bowl-like 3D Mg(BH4 )2 –NaBH4 –FG composite can be formed after ball-milling. The novel Mg(BH4 )2 –NaBH4 –FG exhibits a low dehydrogenation temperature of 114.9 °C with 6.9 wt% of pure hydrogen in seconds. In-depth investigations show that such greatly improved hydrogen desorption properties of the Mg(BH4 )2 –NaBH4 –FG composite could be ascribed to both the "novel bowl-like 3D structure" with large specific surface area and the "reactant destabilized modification" owing to the decrease of the reaction enthalpy caused by the formation of NaMgF3 . This finding provides a facile preparation of complex borohydride composites with low dehydrogenation temperature and fast rate, which accelerates its practical application in fuel cells.